A Hematological study on the effect of environmental stress on cockerel bird (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The effects of pollution on cockerel birds, which have their own distinct physiological andhematological features, have not received as much attention as they deserve. In my study, Hematologyand development performance in birds like Cockerels are negatively impacted by this sort of pollution.Its sound waves also have an effect on the inner ear hair cells that translate between various pitchranges. Cockerels, or male chickens, serve an important purpose in farming and poultry production. Notonly can you consume them, but they also help increase the variety of chicken breeds available. Theirwell-being is, therefore, essential to the continued success of these sectors. Hematological studies wereperformed on the blood drawn from the brachial veins of both the control and experimental birds thenext day, following the protocol described by Singh et al. (2003). In present investigation, I have studiedhazards of generator caused in the form of air pollution and sound pollution. This type of pollutionadversely affects the hematology of avian species as Cockerel birds and their growth performance.Beside, its sound also affects on the inner ear hair cells which are responsible for receiving sound ofdifferent frequencies.